Optimalisasi Pemanfaatan Media GeoGebra dan Lembar Kerja Peserta Didik (LKPD) untuk Meningkatkan Pemahaman Materi Dimesi Tiga - Sari, Noviana Puspita; Tyaningsih, Ratna Yulis (Griya Journal of Mathematics Education and Application, 2024)
This research discusses the design and implementation of GeoGebra media and Student Worksheets (LKPD) for three-dimensional material. The main focus is to explore the potential use of media, such as 3D simulations, learning videos, and mathematical modeling applications, in increasing students' understanding of complex concepts. This research aims to analyze the benefits of using media in LKPD, including increasing student involvement, facilitating abstract understanding, and developing critical thinking skills. The research method used is Research and Development (R&D), which involves the needs analysis, design, development, implementation and evaluation stages. The research subjects consisted of 30 students taking the Mathematics Teaching Materials course. Data was collected through a questionnaire on student responses to the media used in the LKPD. The research results show that the use of media in LKPD significantly increases understanding of three-dimensional concepts. In addition, students responded positively to the use of media, which was considered to help visualize concepts and increase interest in learning. Media implementation strategies in LKPD, such as demonstrations, group assignments and class discussions, have proven effective in overcoming the challenges of three-dimensional mathematics learning. Thus, media integration in LKPD is recommended as an effective strategy to increase students' understanding and involvement in mathematics learning.